Cystic Hygroma Treated with Homoeopathic Medicines: Best Case Series (Advancements in Homeopathic Research, 2022)
It is a retrospective study of cases of Cystic Hygroma treated in Gaurang Clinic & Centre for Homoeopathic Research, Kapoorthala, Aliganj, Lucknow. The main parameter of assessment was visual i.e. photography. Seven well followed up cases which responded to constitutional homoeopathic treatment are presented with photographic evidence. Results are positive and reproducible [1][2]. The time duration of treatment varied from case to case irrespective of size of the lesion.
Keywords: Cystic Hygroma; lymphangioma; Homoeopathic Research